2017
DOI: 10.21037/acs.2017.10.02
|View full text |Cite
|
Sign up to set email alerts
|

Non-cardiac manifestations of Marfan syndrome

Abstract: Because of the widespread distribution of fibrillin 1 in the body, Marfan syndrome (MFS) affects virtually every system. The expression of this single dominantly inherited gene is variable within a family, and between families. There is some genotype-phenotype correlation which is helpful in guiding long-term prognosis, and management. In general gene mutations have been reported in clusters, with those having mainly ocular manifestations occurring in exons 1 to 15 of this 65-exon gene; those causing cardiac p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 73 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Although no longer a formal contributor to the systemic score, when combined with other reported orthodontic features such as cross-bite, Class II molar occlusion, and potential increased risk of dental caries, it appears that oral manifestations of MFS are often identifiable on routine examination [ 95 , 104 , 105 ]. An awareness of these features among dental practitioners and orthodontists is helpful for raising the suspicion of MFS due to the risk of bacterial endocarditis in those with heart valve involvement, which may warrant antibiotic prophylaxis [ 3 , 105 , 106 ].…”
Section: Craniofacialmentioning
confidence: 99%
“…Although no longer a formal contributor to the systemic score, when combined with other reported orthodontic features such as cross-bite, Class II molar occlusion, and potential increased risk of dental caries, it appears that oral manifestations of MFS are often identifiable on routine examination [ 95 , 104 , 105 ]. An awareness of these features among dental practitioners and orthodontists is helpful for raising the suspicion of MFS due to the risk of bacterial endocarditis in those with heart valve involvement, which may warrant antibiotic prophylaxis [ 3 , 105 , 106 ].…”
Section: Craniofacialmentioning
confidence: 99%
“…13 participants were parents of children with idiopathic scoliosis and three were parents of children with additional comorbid conditions; these were Marfan syndrome, Chiari malformation, and autism spectrum disorder (ASD). Sixty percent of those diagnosed with Marfan syndrome have scoliosis (Child, 2017), and Chiari malformations are also associated with scoliosis (Kelly et al, 2015). A systematic review in 2019 addressing spinal deformities and ASD indicated that, although many children with ASD have postural disorders and there is some evidence in clinical settings that these conditions can co-exist, the association between these two disorders is understudied and prevalence is currently unknown (Trentin et al, 2019).…”
Section: Description Of Participantsmentioning
confidence: 99%
“…It has been assumed that connective tissue abnormality can contribute to urinary incontinence [247,248], and a high prevalence of urinary incontinence has been reported in women with Marfan syndrome [247][248][249]. However, urinary incontinence is common in women in general and the estimated prevalence varies depending on several factors, among them the population studied.…”
Section: Urinary Incontinencementioning
confidence: 99%
“…Fibrillin insufficiency in the periosteum and inserting muscles, improper response to deficient tension in periosteum and sutures leading to 'long face' growth or oral breathing are suggested explanations [291]. (Table 1) Deviated nasal septum and sinusitis have been described as common, and allegedly large tonsils and adenoids can contribute to otitis in Marfan syndrome [292]. However, there are no data to confirm this.…”
Section: Craniofacial Featuresmentioning
confidence: 99%